2011
DOI: 10.1007/s12576-011-0171-x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-induced changes in blood flow in STZ-diabetic and non-diabetic rats: relation to nitric oxide synthase and cyclooxygenase inhibition

Abstract: In this study, using the microsphere method, the hemodynamic response to endothelin-1 (ET-1) in healthy and streptozotocin (STZ)-diabetic rats was evaluated as well as the influences of inhibition of nitric oxide (NO)-synthase using L-NAME (Nω-nitro-l-arginine methyl ester) and the cyclooxygenase inhibitor indomethacin. Blood flow (Q) was measured in tissues of interest for vascular complications in diabetes such as kidney, eye, brain, heart and skeletal muscle with the main focus on ophthalmic circulation. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
2
3
1
Order By: Relevance
“…We do not know the exact cause for these observations, and can only speculate that it may be a consequence of pump malfunction, or a delayed response to the adenosine. In a previous study, Granstam and Granstam reported a 60% decrease in blood flow at similar dose using microsphere analysis following the L‐NAME injection (dose), which was a larger change than we have observed. However, they have followed the bolus L‐NAME injection with an infusion for 10 min at a rate of 10 mg/kg.…”
Section: Discussioncontrasting
confidence: 46%
“…We do not know the exact cause for these observations, and can only speculate that it may be a consequence of pump malfunction, or a delayed response to the adenosine. In a previous study, Granstam and Granstam reported a 60% decrease in blood flow at similar dose using microsphere analysis following the L‐NAME injection (dose), which was a larger change than we have observed. However, they have followed the bolus L‐NAME injection with an infusion for 10 min at a rate of 10 mg/kg.…”
Section: Discussioncontrasting
confidence: 46%
“…For L‐NAME, the dosage of 25 mg/kg caused a decrease of 55% in RBP 40 min after L‐NAME delivery (Figure 7A). The ~ 55% change is similar to the change of ~ 60% with the same dose reported in Granstam and Granstam 58 . As shown in Figure 7, the pharmacological agent‐induced RBP changes measured by FAIR ASL are similar to the RBF changes induced by the same agents with the same delivery protocol measured by the invasive flow probe method.…”
Section: Discussionsupporting
confidence: 78%
“…In the study by Granstam et al , diabetic rats exhibited decrease renal blood flow as compared with non-diabetic rats, providing evidence of vasoconstriction in the context of diabetes. Treatment of diabetic rats with the ET A receptor antagonist BQ-123 implied no alteration in renal blood flow [ 72 ]. However, in isolated glomeruli from diabetic rats albumin permeability was increased, while treatment with BQ-123 significantly reduced the albumin permeability in a dose-dependent manner [ 37 ].…”
Section: Endothelin Antagonists In Diabetic Nephropathymentioning
confidence: 99%